Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.ijhydene.2011.10.047
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced hydrogen uptake/release in 2LiH–MgB 2 composite with titanium additives

Abstract: The influence of different titanium additives on hydrogen sorption in LiHeMgB 2 system has been investigated. For all the composites LiHeMgB 2 eX (X ¼ TiF 4 , TiO 2 , TiN, and TiC), prepared by ball-milling in molar ratios 2:1:0.1, Þve hydrogen uptake/release cycles were performed. In-situ synchrotron radiation powder X-ray diffraction (SR-PXD) and attenu-ated total reßection infrared spectroscopy (ATR-IR) have been used to characterize crystal phases developed during the hydrogen absorptionedesorption cycles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
(36 reference statements)
1
16
0
Order By: Relevance
“…Recent studies found that addition of a small amount of transition metal (TM) compounds can markedly shorten or even eliminate the incubation period. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] According to Bo ¨senberg and coworkers, the various TM additives may share a common promoting mechanism, that is, formation of TM borides which act as heterogeneous nucleation sites for the MgB 2 product. [31][32][33][34] These studies elucidated a seeding approach for improving the reversible dehydrogenation property of the 2LiBH 4 -MgH 2 composite.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found that addition of a small amount of transition metal (TM) compounds can markedly shorten or even eliminate the incubation period. [28][29][30][31][32][33][34][35][36][37][38][39][40][41] According to Bo ¨senberg and coworkers, the various TM additives may share a common promoting mechanism, that is, formation of TM borides which act as heterogeneous nucleation sites for the MgB 2 product. [31][32][33][34] These studies elucidated a seeding approach for improving the reversible dehydrogenation property of the 2LiBH 4 -MgH 2 composite.…”
Section: Introductionmentioning
confidence: 99%
“…This reaction is generally accepted [22,23,[25][26][27][28][29][30][31][32] as representative of the absorption process and proceeds as a one-step reaction [25,28]. However, it was first suggested by Vajo et al [22] that between 400 and 450 °C a two-plateau region should exist.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetic properties of the system are influenced fundamentally by temperature and pressure. However, they are also affected by many other factors, including, for example, the reacted fraction, use of additives (catalysts) [22,[25][26][27][28][29][30][31][32]34], microstructure, particle size distribution [35], cycle number [9], and degree of compaction [36], among others.…”
Section: Introductionmentioning
confidence: 99%
“…However, the real kinetics of the undoped Li‐Mg‐B‐H system is sluggish and high temperature is needed to give an acceptable dehydrogenation rate. Thereby, great efforts have been devoted to exploring efficient additives, which can be classified as chlorides, fluorides, and oxides . Undoubtedly, these additives improved the kinetics of RHC systems.…”
mentioning
confidence: 99%
“…Yet, almost all of these dopants will generate some by‐products, which will take up some weight in the system, causing a decrease of reversible hydrogen storage capacity . Besides, to get an improved kinetics, activation process is needed . Moreover, the kinetics and cycling stability should be further improved for its practical application.…”
mentioning
confidence: 99%